ABREVIATION USED DURING THE COVID-19 PANDEMIC: PROCESS OF ESTABLISHMENT AND IMPACT OF USE - Sri Wahyuni; Ria Febrina (LLDIKTI Wilayah X, 2022)
The Covid-19 pandemic has led to several abbreviations' emergence. Some abbreviations come from English and also from Indonesian. This phenomenon has a social and psychological impact on society. Therefore, it is necessary to analyze the abbreviations used during the Covid-19 pandemic based on morphological studies. This study describes the used abbreviations, the forming process, and the impact on the Indonesian people's life. The data collected in this study used the listening method with tapping techniques, followed by the observation without interview and the note-taking approach. Then, it conducted the data analysis with a data flow model analysis and a referential equivalent method. Moreover, these methods used determination elements as a primary approach and differential comparative as a secondary approach. Later, this study performed the data presenting with the informal methods by giving data analysis in sentences. The results showed several abbreviations: IMR, PPE, BLT, CCT, 3K, 3M, 3T, J3K, 3T+3M–3K, banpres, Covid-19, daring, isoman, and so on. This forming process occurred through abbreviations, acronyms, and a combination of abbreviations and acronyms. Hence, the formation of abbreviations related to Covid-19 impacts people's lives, both socially and psychologically.